We'll always have poison - Magnani, Barbarajean (Encircle Publications, 2024)
"A world-renowned climatologist is found dead off the Great Barrier Reef of northern Australia weeks before he' s set to deliver his earth-shattering findings at the international Climate Council conference. Was it greed to maintain the status quo of fossil fuels- or revolutionary new science- that motivated his murder? Can Lily Robinson stop the killer before another climate scientist dies? With operative and lover JP Marchand at her side, Lily uncovers a cunning plot that endangers world order, and changes the trajectory of her life- forever."--amazon.com.